Experiential Learning in Mobile Technologies - kanta Dash, Mukti; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
Experiential learning is the way toward making creating knowledge through the change of experience and understanding and it has been received in an expanding number of areas. This paper explores the technological support probability for experiential learning. A learning movement flow and a "mobile technology system" were intended to encourage the students in the experiential learning. An analysis was led on 2 classes of fifth-grade at a primary school, one class utilizing "personal digital assistants (PDAs)" and another working without them. The outcomes demonstrate that mobile technologies are compelling in improving creation of knowledge during experiential learning. The interchange between the proposed learning flow and affordances of mobile technology for experiential learning is altogether examined